Distributed temperature sensing and fault-tolerant logging for PVC-based smoke condensers using dual-channel type-K sensors - Setyawan, Reinaldi Teguh; Umira, Siti; Kurniawan, Irwan; Gunawan, Gunawan; Muthoriq, Ery (Jurnal Polimesin, 2025)
The condensation process of smoke in charcoal-burning systems generates high temperatures that pose a critical thermal risk to PVC piping, which has a melting point of 85 °C. This study presents the design and implementation of a distributed temperature sensing system using dual-channel Type-K thermocouples controlled by an Arduino Uno microcontroller. The system is equipped with fault-tolerant logging and real-time monitoring features, utilizing the MAX6675 thermocouple amplifier module for digital signal acquisition. Two sensors are strategically placed along the smoke conduit to capture temperature differentials between primary and secondary zones. Experimental testing was conducted over six consecutive days with data acquisition sessions at noon and midnight. The highest recorded temperature from the primary sensor reached 83.75 °C, while the secondary sensor recorded significantly lower values, indicating a thermal gradient of 23.8 °C between inlet and outlet. Comparative calibration using an umbrella-type analog thermometer revealed a minimal deviation of 0.41 °C, confirming the system’s accuracy. Two sets of error profiling showed variations in measurement consistency, with average error rates of 13.79% and 5.93% across a 30 °C–80 °C reference range. Voltage stability was maintained throughout all test scenarios, with a constant 5 V input and 4.4 V output. The system successfully demonstrated its ability to perform dual-point thermal detection with resilient performance under fluctuating combustion conditions. This sensor-integrated platform is well-suited for thermal protection and early intervention in biomass-based liquid smoke condensation systems, particularly in small-scale applications using low-melting-point materials such as PVC.